Substantionation of the Transformation of the Priorities of Innovation and Technological Development of Russian Regions in the Global Crisis - Sukhovey, Alla Filippovna; Golova, I.M. (Economy of Regions, 2016)
The purpose of the study is the substantiation of the necessity to implement the policy of neo-industrialization in Russia as a tool for overcoming the consequences of the global crisis. The hypothesis of the study consists in the assumption that the increase of Russian regions’ competitiveness during the crisis is impossible without the transformation of regional innovation priorities with the account of the modern trends in science and technology development as well as the production needs in modernization and import substitution, rapidformation of the high-tech sector. The authors suggest that one of the main reasons for modern structural crisis in the Russian Federation is ignoring of the determined impact of the level of innovative-technological development on the status of regional socio-economic systems and the country as a whole. During the test of the hypothesis, on the basis of the analysis of official statistics, there are revealed a number of negative trends that hinder overcoming the crisis by the accelerated development of modern technological waves in Russia. They are the staff reduction in the Russian science and deterioration of its quality; the increasing gap between the financial support of the scientific research in the Russian Federation and in the developed countries; the reduction of the possibility for the development of innovative business; producers’ disincentive in the innovative activities. The authors substantiate the necessity to strengthen the state innovative policy for the improvement of the socio-economic situation in the Russian Federation. The research proposes the methodological approach to the selection of the priorities for the innovative support of the economic development of the Russian regions based on a comprehensive consideration of the status and problems of the development of scientific and innovative capacity, business environment of the region, as well as its ability to create the innovative production. The calculations to assess the possibility to form the innovative activity’s centres of different types in the Russian regions are made. These centres should be aimed at increasing the share of high-tech enterprises focused on the creation of innovations to solve the current problems for Russia such as import substitution and neo-industrialization of the economy. The article is addressed to the professionals in the field of theory and practice of the management of innovative processes.